ARTIFICIAL INTELLIGENCE AND ELECTIONS IN BRAZIL: ANALYSIS OF THE SCIENTIFIC LITERATURE INDEXED IN THE DIMENSIONS PLATFORM - Leite Alves, Eduardo; Vitor Sobral, Natanael; Alencar Furtado Leite, Anna Carolina; Hillmann Xavier, José Augusto (Suffragium - Scientific Journal of the Regional Electoral Court of Ceará (TRE-CE), 2026)
The advancement of artificial intelligence (AI) has directly impacted the Brazilian electoral landscape, increasing both campaign efficiency and risks to democracy. This study aimed to analyze how the scientific literature addresses the relationship between AI and Brazilian elections. To this end, a descriptive study was conducted using a bibliometric approach and qualitative analysis, with search and retrieval carried out on the Dimensions platform. The results show that the literature is organized into three main dimensions: technological-electoral (AI and the electoral process), democratic-informational (democracy and disinformation), and legal-regulatory (electoral advertising and regulation). The literature highlights the dual nature of AI: while it optimizes campaigns, it also enables practices such as bots, deepfakes, and microtargeting of fake news. Although the Superior Electoral Court (TSE) has adopted regulatory measures, evidentiary challenges and normative conflicts persist. It is concluded that democratic preservation depends on the articulation between technological innovation, effective regulation, and media literacy.